GAMBARAN KETERAMPILAN SELF REGULATED LEARNING SISWA SMP KELAS VIII SELAMA PEMBELAJARAN DARING - Syifa Dewi Gustiana; Euis Eti Rohaeti; Tuti Alawiyah (IKIP Siliwangi, 2023)
This study purpose to describe the self regulated learning skills of grade VIII junior high school students during online learning at SMP Negeri 9 Cimahi. This research is based on the reality at school, where there are a number of students who have a level of self regulated learning below the average while participating in online learning. The method used in this research is a qualitative method with a descriptive type of research. This study uses interview and observation techniques to collect data. The informants in this study were junior high school students grade VIII totaling 3 people with the criteria of having low self-regulated learning during online learning. In terms of metacognitive, motivational and behavioral aspects, the results of this study indicate that during online learning, students find it difficult to organize themselves in independent study sessions. This study also found internal factors and external factors as two factors that affect students' self regulated learning. Keywords: Online Learning, Self Regulated Learning